2008
DOI: 10.1021/ja077972s
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Catalysis of Anti-Cocaine Catalytic Antibody: Competing Reaction Pathways and Free Energy Barriers

Abstract: The competing reaction pathways and the corresponding free energy barriers for cocaine hydrolysis catalyzed by an anti-cocaine catalytic antibody, mAb15A10, were studied by using a novel computational strategy based on the binding free energy calculations on the antibody binding with cocaine and transition states. The calculated binding free energies were used to evaluate the free energy barrier shift from the cocaine hydrolysis in water to the antibody-catalyzed cocaine hydrolysis for each reaction pathway. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 60 publications
(126 reference statements)
0
96
1
Order By: Relevance
“…Finally, the measured (Ϫ)-cocaine concentration-dependent radiometric data were analyzed by using the standard Michaelis-Menten kinetics so that the catalytic parameters were determined along with the use of a well established standard enzyme-linked immunosorbent assay protocol (Pan et al, 2008 …”
Section: In Vitro Activity Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the measured (Ϫ)-cocaine concentration-dependent radiometric data were analyzed by using the standard Michaelis-Menten kinetics so that the catalytic parameters were determined along with the use of a well established standard enzyme-linked immunosorbent assay protocol (Pan et al, 2008 …”
Section: In Vitro Activity Testsmentioning
confidence: 99%
“…Therefore, starting from the A328W/Y332A or A328W/ Y332G mutant, rational design of BChE mutants against (Ϫ)-cocaine has been focused on decreasing the energy barrier for the first reaction step without significantly affecting the other reaction steps. We have developed unique computational strategies and protocols based on the virtual screening of rate-determining transition states of the enzymatic reaction to design enzyme mutants with improved catalytic activity (Pan et al, 2005(Pan et al, , 2007(Pan et al, , 2008Zheng et al, 2008Zheng et al, , 2010Yang et al, 2009). The computational design was followed by in vitro experiments, including site-directed mutagenesis, protein expression, and fast enzyme activity screening using the culture medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DANA is a sialidase inhibitor, an uncleavable analogue of transitional state intermediate during sialic acid trimming [27]. Recent studies have shown that by utilizing haptens for immunization one can induce abzymes with exotic specificities, such as hydrolyzing cocaine [28,29] or organophosphorus nerve poisons [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been difficult to improve the CAb activity further because a CAb, unlike an enzyme, can help stabilize the transition state only for nonenzymatic cocaine hydrolysis; a mechanistic study (20) indicates there is no formation of a covalent bond or breaking between the substrate and CAb during the reaction process.…”
Section: Significancementioning
confidence: 99%